136 Nutritive value of phytase- and multi-carbohydrase-supplemented carinata meal for growing pigs. (5th December 2019) - Hong, Jinsu; Lee, Jung Wook; Pettersson, Dan; Woyengo, Tofuko A
Abstract: Objective of the study was to determine the effect of supplementing a combination of phytase and multi-carbohydrase on standardized ileal digestibility (SID) of amino acid (AA) and net energy (NE) value of carinata meal for growing pigs. Ten ileal-cannulated barrows (initial body weight = 53.9 ± 4.76 kg) were fed 4 diets in a replicated 4 × 4 Latin square design with 2 additional columns to give 10 replicates per diet. Diets included a corn-soybean meal (SBM)-based basal diet, the basal diet with 25% carinata meal, basal diet with 25% carinata meal plus phytase at 2, 000 FTU/kg and multi-carbohydrase at 0.2g/kg, and a nitrogen-free diet. The multi-carbohydrase supplied 4 units of xylanase, 10 units of β-glucanase, and 1000 units of pectinase per kilogram of diet. The ratio of corn to soybean meal and soybean oil in carinata meal- containing diets was identical to that in the corn-soybean meal based basal diet to allow calculation of AA and energy digestibility of carinata meal by the difference method. On a DM basis, carinata meal contained 50.2% CP, 0.88% ether extract, 15.37% ADF, 1.82% Lys, 0.96% Met, 1.89% Thr, and 0.64% Trp, respectively. The SID of Lys, Met, Thr, and Trp for carinata meal were 51.4%, 82.2%, 65.9%, and 85.9%, respectively. Supplementation of a combination of phytase and multi-carbohydrase did not affect the SID of AA for the corn-SBM-carinata meal-based diet, and for the carinata meal. However, supplementation of a combination of phytase and multi-carbohydrase improved (P = 0.015) the apparent total tract digestibility of gross energy, and DE and NE values for carinata meal by 9.4, 9.5, and 12.4% respectively. In conclusion, the enzymes used in the current study could be added in carinata meal-based diets for pigs to improve the energy value of the carinata meal.